The Influence of Entrepreneurship Education, Environment and Self Efficacy on Interest in Entrepreneurship: Pengaruh Pendidikan Kewirausahaan, Lingkungan dan Self Efficacy Terhadap Minat Berwirausaha - Aisy, Rohadatul; Sumartik, Sumartik (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the Effect of Entrepreneurship Education, Environment, and Self Efficacy on Interest in Entrepreneurship (Study on Management Study Program Students, Faculty of Business, Law and Social Sciences, University of Muhammadiyah Sidoarjo Batch 2018). Law and Social Sciences, University of Muhammadiyah Sidoarjo Class 2018. This research uses quantitative research. The sampling technique used is the slovin formula with a total sample of 210 students of the Management Study Program, Faculty of Business, Law and Social Sciences Class of 2018. The data collection technique used a questionnaire which was measured using a Likert scale and tested for reliability and validity. The data analysis technique used is multiple linear regression analysis. The results of this study prove that entrepreneurship education has an effect on interest in entrepreneurship, environment affects interest in entrepreneurship, self-efficacy affects entrepreneurship. Simultaneously, entrepreneurship education, environment, and self-efficacy affect the interest in entrepreneurship.